PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, KOMISARIS INDEPENDENDAN UKURAN PERUSAHAAN TERHADAP INTEGRITAS LAPORAN KEUANGAN: Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Plastik dan Kemasan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019 (STIE Rajawali Purworejo, 2021)
This study aims to examine the effect of institutional ownership, managerial ownership, independent commissioners and company size on the integrity of financial statements (in the plastic and packaging sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The population in this study is the plastics sub-sector company. and packaging listed on the Indonesia Stock Exchange (IDX) in 2017-2019 were 15 companies. The sampling method used was purposive sampling, where samples that met the criteria were 6 companies over a period of 3 years, so the number of samples of research data was 18. The analysis technique used is multiple correlation analysis, multiple linear regression analysis, coefficient of determination, t test and f test. The results of this study indicate that institutional ownership, managerial ownership, independent commissioners and company size affect the integrity of financial statements.